Root induction of Phalaenopsis amabilis with various types and concentration of banana extract by in vitro - AISAR NOVITA; WILLY EKA PRASETYA; WAN ARFIANI BARUS (Jurnal Natural, 2022)
Root induction is an important step in plant propagation in vitro. Root stimulation can occur in the presence of the hormones auxin and gibberellins which can be obtained from other plants, one of which is bananas. The research aims to determine the effect of various species and concentrations of the banana extract on Phalaenopsis amabilis root induction in vitro. The research was conducted in the Laboratory of Tissue Culture Alifa Agricultural Research Center (AARC), Medan, North Sumatera, from May until July 2020. The research used a Factorial Completely Randomized Design (CRD) with 2 factors, the first factor was the type of banana extract with 3 levels, consisting of Ambon, Raja, and Kepok. The second factor is the concentration of banana extract (C) with 4 levels, consisting of 50 g/l, 100 g/l, 150 g/l, 200 g/l. The results showed that the concentration of banana extract had a significant effect on the number of roots, but various species of bananas and the interaction of the species of bananas and concentration banana extract had no significant effect on root induction